2014
DOI: 10.1364/oe.22.029746
|View full text |Cite
|
Sign up to set email alerts
|

Optical sorting of nonspherical and living microobjects in moving interference structures

Abstract: Contactless, sterile and nondestructive separation of microobjects or living cells is demanded in many areas of biology and analytical chemistry, as well as in physics or engineering. Here we demonstrate advanced sorting methods based on the optical forces exerted by travelling interference fringes with tunable periodicity controlled by a spatial light modulator. Besides the sorting of spherical particles we also demonstrate separation of algal cells of different sizes and particles of different shapes. The th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…20). This feature has been used for the selective transport of particles based on their size, shape or optical properties [16,103,106,[315][316][317][318][319], and the method is also referred to as passive optical sorting [21,104].…”
Section: Interface-constrained Transport With Optical Forcesmentioning
confidence: 99%
“…20). This feature has been used for the selective transport of particles based on their size, shape or optical properties [16,103,106,[315][316][317][318][319], and the method is also referred to as passive optical sorting [21,104].…”
Section: Interface-constrained Transport With Optical Forcesmentioning
confidence: 99%
“…In the field of optical trapping, Ashkin et al discovered the existence of radiation pressure in 1970s and demonstrated a technique now referred to as optical tweezers in 1980s [22,23]. Since then, optical trapping have attracted tremendous interest in both fundamental research and device application [24][25][26][27]. In conventional optical tweezers, the balance between gradient force and scattering force is exploited to capture particles.…”
Section: Introductionmentioning
confidence: 99%
“…Jákl et al [142] have demonstrated a sorting method using optical forces exerted by travelling interference fringes. The periodicity of the fringes was modulated by an SLM.…”
Section: Optical Manipulation and Sortingmentioning
confidence: 99%